GAMBARAN BURNOUT PERAWAT PELAKSANA DI RUANG INTENSIF RSUP SANGLAH DENPASAR - Ni Made Nopita Wati; Ni Luh Putu Thrisna Dewi; Aeny Suryanti (Jurnal Kesehatan dr. Soebandi, 2020)
Introduction:The complexity of duties and obligations, the high level of patient dependence on nurses in the intensive room, as well as the limited time they have to rest, causes nurses in the intensive room to lack time to complete nursing tasks which incidentally must be completed quickly and precisely so that nurses tend to experience burnout. The purpose of this study was to determine the burnout overview of implementing nurses in the Intensive Room. Method:The design of this research is quantitative descriptive research with cross sectional approach. The sample in this study was selected by a total sampling technique of 121 people. The Result: Results of this study are intensive nurses experiencing emotional exhaustion in the high category as many as 52 people (43%), depersonalization in the high category as many as 57 people (47.1%) and decreased personal achievement in the high category as many as 55 people (45 , 5%). Discussion:The results of this research are expected to be the management of Sanglah Hospital can conduct activities for refreshment such as outbound or family gathering and the need for additional nurses in the intensive room.